Comparison of rescue medication prescriptions in patients with chronic obstructive pulmonary disease receiving umeclidinium/vilanterol versus tiotropium bromide/olodaterol in routine clinical practice in England - Requena, Gema; Czira, Alexandrosz; Banks, Victoria; Wood, Robert; Tritton, Theo; Castillo, Catherine M.; Yeap, Jie; Wild, Rosie; Compton, Chris; Rothnie, Kieran J.; Herth, Felix; Quint, Jennifer K.; et al. (The International journal of chronic obstructive pulmonary disease, 2023)
Purpose: Routinely collected healthcare data on the comparative effectiveness of the long-acting muscarinic antagonist/long-acting β2-agonist combination umeclidinium/vilanterol (UMEC/VI) versus tiotropium bromide/olodaterol (TIO/OLO) for chronic obstructive pulmonary disease (COPD) is limited. This study compared rescue medication prescriptions in patients with COPD in England receiving UMEC/VI versus TIO/OLO. Patients and Methods: This retrospective cohort study used primary care data from the Clinical Practice Research Datalink Aurum database linked with secondary care administrative data from Hospital Episode Statistics. Patients with a COPD diagnosis at age ≥ 35 years were included (indexed) following initiation of single-inhaler UMEC/VI or TIO/OLO between July 1, 2015, and September 30, 2019. Outcomes included the number of rescue medication prescriptions at 12-months (primary), and at 6-, 18- and 24-months (secondary), adherence at 6-, 12-, 18- and 24-months post-index, defined as proportion of days covered ≥ 80% (secondary), and time-to-initiation of triple therapy (exploratory). Inverse probability of treatment weighting (IPTW) was used to balance potential confounding baseline characteristics. Superiority of UMEC/VI versus TIO/OLO for the primary outcome of rescue medication prescriptions was assessed using an intention-to-treat analysis with a p-value < 0.05. Results: In total, 8603 patients were eligible (UMEC/VI: n = 6536; TIO/OLO: n = 2067). Following IPTW, covariates were well balanced across groups. Patients initiating UMEC/VI had statistically significantly fewer (mean [standard deviation]; p-value) rescue medication prescriptions versus TIO/OLO in both the unweighted (4.84 [4.78] vs 5.68 [5.00]; p < 0.001) and weighted comparison (4.91 [4.81] vs 5.48 [5.02]; p = 0.0032) at 12 months; consistent results were seen at all timepoints. Adherence was numerically higher for TIO/OLO versus UMEC/VI at all timepoints. Time-to-triple therapy was similar between treatment groups. Conclusion: UMEC/VI was superior to TIO/OLO in reducing rescue medication prescriptions at 12 months after treatment initiation in a primary care cohort in England, potentially suggesting improvements in symptom control with UMEC/VI compared with TIO/OLO.
Veröffentlicht: 13. Juli 2023
Gesehen am 22.08.2023